Binary Nonlinearization for AKNS-KN Coupling System. (14th June 2014) - Wang, Xiangrong; Zhang, Xiaoen; Zhao, Peiyi
Abstract : The AKNS-KN coupling system is obtained on the base of zero curvature equation by enlarging the spectral equation. Under the Bargmann symmetry constraint, the AKNS-KN coupling system is decomposed into two integrable Hamiltonian systems with the corresponding variables x, t n and the finite dimensional Hamiltonian systems are Liouville integrable.